Non-Wettable Microporous Sheets Using Mixed Polyolefin Waste for Oil–Water Separation - Junaid Saleem (14670322) (2023)
Mixed polyolefin-based waste needs urgent attention to mitigate its negative impact on the environment. The separation of these plastics requires energy-intensive processes due to their similar densities. Additionally, these materials cannot be blended without compatibilizers, as they are inherently incompatible and immiscible. Herein, non-wettable microporous sheets from recycled polyethylene (PE) and polypropylene (PP) are presented. The methodology involves the application of phase separation and spin-casting techniques to obtain a bimodal porous structure, facilitating efficient oil–water separation. The resulting sheets have an immediate and equilibrium sorption uptake of 100 and 55 g/g, respectively, due to the presence of micro- and macro-pores, as revealed by SEM. Moreover, sheets possess enhanced crystallinity, as evidenced by XRD; hence, they retain their structure during sorption and desorption and are reusable with 98% efficiency. The anti-wetting properties of the sheets are enhanced by applying a silane coating, ensuring waterless sorption and a contact angle of 140°. These results highlight the importance of implementing sustainable solutions to recycle plastics and mitigate the oil spill problem. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym15143072